ANALISIS MAKNA DIKSI LIRIK LAGU â€œSATUâ€ MILIK DEWA 19 DENGAN MENGGUNAKAN PENDEKATAN SEMIOTIK - Mimin Mimin; Wikanengsih Wikanengsih; Aditya Permana (IKIP Siliwangi, 2022)
A song that has lyrics with a deep meaning or meaning is always popular even though it has been lyrical for a long time, in the creation of song lyrics, there are language games such as games in language style and word meanings. Dhani's songs with Dewa 19 are often judged to have controversial lyrics in the lyrics, the word